A semi-empirical approach to the prediction of deformation behaviors of β-Ti alloys. (1st January 2019) - Wang, C.H.; Russell, A.M.; Cao, G.H.
Abstract: A semi-empirical approach based on the compositional average electron-to-atom ratio ( e / a ¯ ) and atomic radius difference ( ∆ r ¯ ) was proposed to refine the "d-electron method". The e / a ¯ − ∆ r ¯ diagram shows that Twinning/Stress-Induced Martensite (SIM) activates when ∆ r ¯  > −2.5, and a low e / a ¯ or absolute value of ∆ r ¯ favors Twinning/SIM by reducing the resistance of lattice shear. In addition to the phase stability, it suggests that the valence electron number and atomic radius of alloying element also determine the deformation mechanism in body-centered cubic Ti alloys. This alloy design method was verified by the tensile results of Ti-4Mo-4Co and Ti-6Mo-4Zr (at.%) alloys. Graphical abstract: Unlabelled Image